Citric acid concentration by electrodialysis: Ion and water transport modelling - Ling, Lay Pee (Elsevier B.V., 2002)
The work in this paper was aimed at the study of the ion transport behaviour of citrate ion through ion exchange membranes. A mathematical model to represent the ion and water transport behaviour of an electrodialysis (ED) process for concentrating citric acid under the influence of different current density was developed. This model is valid for any ED process with ion exchange membranes used under a similar operating condition. The value for the phenomenological coefficients is different for other types of membranes and solutes. The corresponding phenomenological coefficients have to be determined experimentally. The reliability of developed ion and water transport model was assessed through comparison with the experimental data. The results obtained showed that the developed ion and water transport model was in good agreement with the experimental data and it could be used to predict the performance of ED for citric acid concentration.